2017
DOI: 10.1016/j.cmi.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Spread of a new Chlamydia trachomatis variant from men who have sex with men to the heterosexual population after replacement and recombination in ompA and pmpH genes

Abstract: Our data would support the evidence that subtype J could be a 'subtype bridge' between different sexual networks, as subtype J has been found in men who have sex with men and heterosexual populations in similar proportions. This work reveals the necessity of implementing molecular surveillance in extra-rectal samples to help us understand the gaps in transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Further, the identification of ST58 (most common in cases of LGV) in two samples containing genotype D suggests recombination between LGV and genotype D strains, or coinfection with strains of both genotypes. Cases of recombination of LGV with other genotypes have been reported previously in Spain [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the identification of ST58 (most common in cases of LGV) in two samples containing genotype D suggests recombination between LGV and genotype D strains, or coinfection with strains of both genotypes. Cases of recombination of LGV with other genotypes have been reported previously in Spain [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the detection of recombinant ompA, a known hotspot for recombination in the C. trachomatis genome, in these samples as part of an approximate 12kb exchange could have only been identified by WGS and not by Sanger sequencing alone, highlighting the genetic resolution achieved in this study to understand the evolution of contemporary C. trachomatis strains 40,43,55 . Some studies have reported recombinant forms of both ompA and pmpH, and tracking these and additional known recombinant variants may inform the field on the dynamics of current transmission networks and C. trachomatis tropism in general 9,53,79 . With that said, the high rates of recombination and limited genetic diversity within C. trachomatis strains indicates the need to include a large number of loci dispersed throughout the genome to circumvent false negativity of clinical strain typing, which can now be efficiently achieved by sequencing the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination is a driver of C. trachomatis evolution [9,12,31]; clinical isolates with recombinations between LGV and urogenital strains have been described [28,30,32], including a recent L2b-D/Da hybrid strain identified in Portugal, which resulted from a recombination across ompA in an L2b genomic background [30]. Therefore, a plausible hypothesis for this observation of these pmpH-ompA discrepancies is that recombination between the genomes of ompA-genotype L2b and ompA-genotype L2 has occurred.…”
Section: Impact Statementmentioning
confidence: 99%